Existence and uniqueness of a classical solution to a functional-differential abstract nonlocal Cauchy problem. (1999) - Byszewski, Ludwik
Abstract : The aim of this paper is to investigate the existence and uniqueness of a classical solution to a functional-differential abstract nonlocal Cauchy problem in a general Banach space. For this purpose, a special kind of a mild solution is introduced and the Banach contraction theorem and a modified Picard method are applied.